Plan de marketing para la Cooperativa de Ahorro y Crédito Quilanga Ltda; del Cantón Quilanga de la Provincia de Loja - Granda Santín, Johana Elizabeth (2017)
The purpose of this research work called: MARKETING PLAN FOR THE COOPERATIVE OF SAVINGS AND CREDIT QUILANGA LTDA; OF CANTÓN QUILANGA OF THE PROVINCE OF LOJA "has as main objective a Marketing Plan that allows the institution to develop and improve the offer of its products and services in the market of Loja, considering that the cooperative is located in the Quilanga and Province of Loja, where the marketing plan will be developed. Methodological and technical tools have been considered such as: the survey aimed at the cooperative's clients, considering a sample of 355 surveys, in order to know the general information of the clients, and interviews with the key factors were carried out to establish Some factors that will benefit the cooperative when offering products and services to its customers. Likewise, the PESTEC analysis was applied to the key informants of the cooperative, which allowed the study of the political, economic, social and cultural, technological and competitive factors to find key information for The cooperative said results allowed to achieve the matrix of the external factor MEFE that results in a value of 2.94 which means that the cooperative has more opportunities such as the development of communications, population growth rate and market to explore and the Threats; Unemployment rate, poverty, labor legislation, gross domestic product and inflation. The competitive analysis of the cooperative itself was carried out, which helped to find very significant results where the main direct cooperative cooperatives could be known as; The cooperative Quilanga, occupying a position of 3.14 leads the market, secondly the cooperative Father Julián Lorente in a position of 3.00 defending aspects found in noticeable disadvantage is the publicity and promotions of the products, thirdly the cooperative Gonzanama with a position Of 2.82 and finally the cooperative Chamber of Commerce of Gonzanama with a position of 2.72. The analysis of the internal factor was executed based on the strengths and weaknesses that the cooperative possesses. For this purpose, we studied each one of the most 5 important variables of the marketing area and in this way we established the internal factor matrix MEFI that gives as a weighted result 2.53 which indicates that the cooperative is slightly stronger than weak, where strengths weigh more as market share, trained personnel, and satisfaction of products and services, and weaknesses weigh less as the lack of Promotions and the lack of consumer analysis and preferences. Next, the market research was carried out to identify and solve the various problems that the cooperative may be experiencing. The strategies to opt as a result of the SWOT and MIE analysis for this were raised four strategic objectives were: Increase profitability even 10% of the cooperative, with a value of $ 1307.50. Achieve a market share of at least 30% of the total population, with an investment of $ 790.00. Position 25% in the minds of customers in the city of Loja at a cost of $ 5546.00 and Improve the quality of products and services offered by the cooperative by implementing new products and services with a value of $ 4305.00. The strategic objectives are set out in operational plans that detail the problem, goal, policy, strategy, tactics, financing, responsibility and cost, providing the Cooperative with the budget required for compliance with the marketing plan for the cooperative. Savings and credit Quilanga Ltda., Is $ 11949.10. Finally, we present the conclusions and recommendations of this study, which concludes that the cooperative has more opportunities such as the development of communications, population growth rate and the market to be explored and the threats of unemployment, labor legislation, gross domestic product, inflation.